2015
DOI: 10.1016/j.psychres.2015.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of suicide attempts in 3.322 patients with affective disorders and schizophrenia spectrum disorders

Abstract: This study explores risk factors for suicide attempts using the electronic health records of 3,322 patients with either schizophrenia spectrum disorders or affective disorders who underwent a comprehensive psychiatric evaluation at the Emergency Department at the Long Island Jewish Medical Center or the Hillside Evaluation Center at The Zucker Hillside Hospital from August 3rd 2011 to July 5th 2012. Multivariate regression analyses showed, after adjusting for sex, that previous suicidal attempts and financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…In patients with severe psychiatric disease, strategies that promote exercise and sport activities, that reduce caffeine consumption and other health-adverse behaviors are particularly important for the reduction of psychotic symptoms, depression, anxiety, low self-esteem, and life dissatisfaction, factors that increase suicide risk. Gallego et al ( 135 ) suggested that in patients with either schizophrenia spectrum disorders or affective disorders, physicians should be alert for the presence of a previous suicidal attempts and financial or relationship losses, factors that can increase suicidal risk. Furthermore, psychiatric hospitalization, a close psychiatric follow up, collaboration with family would be important strategies in reducing the risk of suicidal behavior in patients affected by severe psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with severe psychiatric disease, strategies that promote exercise and sport activities, that reduce caffeine consumption and other health-adverse behaviors are particularly important for the reduction of psychotic symptoms, depression, anxiety, low self-esteem, and life dissatisfaction, factors that increase suicide risk. Gallego et al ( 135 ) suggested that in patients with either schizophrenia spectrum disorders or affective disorders, physicians should be alert for the presence of a previous suicidal attempts and financial or relationship losses, factors that can increase suicidal risk. Furthermore, psychiatric hospitalization, a close psychiatric follow up, collaboration with family would be important strategies in reducing the risk of suicidal behavior in patients affected by severe psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…O t h e r r i s k fac to r s A history of suicide attempts is a well-known predictor for future suicide attempts in patients with psychiatric disorders (Gallego et al, 2015). Previous expression of suicidal behavior and a past history of self-harm have also been reported as risk factors for suicide in patients with dementia.…”
Section: Predictors and Risk Factors Of Suicidal Intentions And Behavmentioning
confidence: 99%
“…No post-hoc definitions of homicidal ideation, intent, or plan or aggression were used for the analyses. Data regarding suicidal ideation and behavior was also collected and has been previously published (Gallego et al, 2015). We obtained information regarding patient diagnosis directly from the EHR.…”
Section: Methodsmentioning
confidence: 99%